INFLUENCE OF ALTITUDE ON FLEXIBILITY OF ELITE WRESTLERS GRECO-ROMAN STYLE - Nikola Nikolov (Journal of Applied Sports Sciences, 2021)
It is widely assumed that wrestling is a sport posing high requirements as regards one’s physical qualities strength and endurance. A lot of specialists, however, point out the necessity of harmonious and balanced development of all motor qualities, including flexibility. This research is aimed at wrestlers’ physical preparation and more specifically the dynamics in the physical quality flexibility. We attempted to find out whether altitude influences the manifestation of the physical quality flexibility and to what extent. The research was done among 13 wrestlers from Bulgarian National team, Greco-Roman style, men. We measured the flexibility of the spinal cord and coxofemoral joint during training camps held at low and high altitude. The tests used (Т1, Т2, Т3 and Т4) are easy to be applied. The results were processed statistically and further discussed. It is clear that there were statistically significant differences only along T2, and there was no reliable difference in the results along the rest of the tests - Т1, Т3 and Т4 at a low and high altitude.